Characterization of the technological domain of relational citation analyses: A study of stem cell patents - Bochi, Fernanda [UNESP]; Grácio, Maria Cláudia Cabrini [UNESP] (Elsevier, 2024)
This research aims to analyze the contribution of univariate and relational citation analysis methods, applied to patents, for the identification and characterization of scientific-technological domains, in documents indexed in the Derwent Innovation Index database. The adopted method was patentometrics associated with bibliometrics, using joint analysis of the relational bibliometric citation methods: co-citation and bibliographic coupling. The corpus of the study is composed of 144 patent families. Through the bibliographic coupling, 5 theme clusters and researchers with well-defined thematic domains were observed. Employing co-citation, 23 clusters were identified, characterizing the epistemic domains related to technological currents in which stem cell inventors operate. Such results allowed us to prospect the scientific-technological scenario in this theme, which can illustrate some institutions’ innovation potentials and explain who the actors at the forefront of such research are. It is proposed that applying this methodology allies to topic modeling techniques.
Keywords: Co-citation analysis; Coupling analysis; Domain analysis; Patentometrics; Patents; Relational citation analysis